Penglibatan Ibu Bapa India Dalam Pendidikan Anak-Anak: Satu Kajian Perbandingan Di Sekolah Jenis Kebangsaan Tamil Dan Sekolah Kebangsaan Di Daerah Kerian, Perak Darul Ridzuan - Vellymalay, Suresh Kumar N. (2011)
This research focuses on parental involvement in National Type Tamil School and National School students’ education at Kerian District, Perak Darul Ridzuan. For the quantitative data collection from the sample of parents, approximately 300 Indian students were selected using stratified random sampling. From this total, 150 students were from National Type Tamil School. They were in Year Three, Four and Five that is 50 students from each Year. The other 150 students were from National School. They were in Year Three, Four and Five that is 50 students from each Year.